2013
DOI: 10.1159/000355542
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis and Urinary Biomarker Assays Reveal Activation of Tubulointerstitial Injury Pathways in a Rodent Model of Chronic Proteinuria (Doxorubicin Nephropathy)

Abstract: Background: Tubular atrophy and interstitial fibrosis are well-recognized sequelae of chronic proteinuria; however, little is known regarding the molecular pathways activated within tubulointerstitium in chronic proteinuric nephropathies. Methods: To investigate the molecular mechanisms of proteinuria-associated tubulointerstitial (TI) disease, doxorubicin nephropathy was induced in rats. Progression of disease was monitored with weekly urinary biomarker assays. Because histopathology revealed multifocal TI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
2
9
0
1
Order By: Relevance
“…Podocyte dysfunction and consequent proteinuria has been recently reinforced as a major determinant of tubular injury, inflammation and apoptosis leading to progressive IFTA [44]. According to our present study and previous literature [45] IFTA developed as part of DXR nephropathy. Urinary NGAL excretion is a sensitive marker of tubular damage not only during acute kidney injury [[46, 47],] but also during IFTA [48].…”
Section: Discussionsupporting
confidence: 78%
“…Podocyte dysfunction and consequent proteinuria has been recently reinforced as a major determinant of tubular injury, inflammation and apoptosis leading to progressive IFTA [44]. According to our present study and previous literature [45] IFTA developed as part of DXR nephropathy. Urinary NGAL excretion is a sensitive marker of tubular damage not only during acute kidney injury [[46, 47],] but also during IFTA [48].…”
Section: Discussionsupporting
confidence: 78%
“…However, the carrier molecules are entrapped within the slit diaphragm due to the size of the carrier molecules used in drug delivery leading to renal tubular tissue injury [ 82 ]. The glomerular and tubular damage observed in our study was similar to the lesion seen in rodent as reported by Cianciolo et al [ 83 ] and Manno et al [ 5 ] in rodent and mini pig animal models, respectively. In addition, our results also agree with the works of Anan et al [ 84 ] as clusters of nuclear material were observed as a result of free radical production from lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%
“…The kidney is also a targeted organ for DOX as previously reported by Salouege et al [ 92 ] and Cianciolo et al [ 83 ], but the order of the DOX organ affinity is less when compared to the heart due to cardiolipin concentration. Zhou et al [ 93 ] demonstrated that the apical region of proximal tubules which have microvillus and abundant podocytes was responsible for the secretion of nephrin and podocin, which are structural components of slit diaphragm.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to the well-recognized DOX-induced cardiotoxicity, DOX causes significant nephrotoxicity characterized by chronic proteinuria, glomerular sclerosis, and interstitial and tubular involvement primarily in rodent models [ 48 50 ]. Similar to DOX-induced cardiotoxicity, oxidative stress is thought to play the major role in mediating DOX-induced nephrotoxicity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%